The structure of parents’ social actions on the zonation policy for new students’ admission - Huda, Syaiful; Ibrahim, Jabal Tarik; Saiman, Saiman; Rojiq, M. Abdul (Interdisciplinary Social Studies, 2024)
This research explores the structure of parents' social actions regarding the zonation policy for new students' admission at SMKN 1 Rejotangan Tulungagung District. The study focuses on the various structures and meanings of the zonation policy, including the New Family Card (KKB), blessings from the school environment (BLS), Keponakan/Niece and Dulur Dewe/Relatives (KDD), Gandheng Gedek or Gandheng Wall (GG/GT), informal entrustment from special persons in government (TWP), special conversations, and special mandate letters from regional government policy makers. According to Max Weber's theory, parents' social actions include taking action with awareness, ensuring they have something right according to the PPDB policy provisions, using methods and techniques, restricting actions to a predetermined time, selecting and assessing actions, hoping for moral principles when making decisions, and learning about social relations between parents and the PPDB committee.